On some species of Astyanax reported erroneously from Argentina - Mirande, Juan Marcos (2015)
Several species of Astyanax have been reported from Argentina which currently are considered not to be distributed so far South or whose identity as Astyanax is doubtful. These records have been copied during decades based on historic accounts or erroneous determination. We conclude that Astyanax bimaculatus, A. fasciatus, A. paranahybae, A. scabripinnis, and A. taeniatus shall be excluded from the faunal lists of Argentina and, at least in the case of A. fasciatus, also of Uruguay.